Implementation of the Law for Police Members Regarding the Sale of Fire-arms and Ammunition (A Case Study at the West Papua Regional Police) - Silubun, Revin Remigius; Renjaan, Henrikus; Silubun, Siria (LEGAL BRIEF, 2025)
This study examines the implementation of criminal law against members of the Indonesian National Police involved in the sale of firearms and ammunition, with a specific case study at the West Papua Regional Police. Using a normative juridical and qualitative approach, the research analyzes the coherence between Emergency Law No. 12 of 1951, Law No. 2 of 2002 on the National Police, and internal regulations such as the Chief of Police Regulations on firearms control and the professional code of ethics, as well as their application in practice. The findings show that the acts of trading and controlling firearms by police officers clearly fulfill the elements of illegal possession and participation in crime, thus giving rise to full criminal and ethical liability. Law enforcement in this case reflects a dual-track accountability system: criminal proceedings before the general court and internal disciplinary and ethical sanctions, including the possibility of dishonorable discharge. However, the case also reveals structural weaknesses in firearms supervision, internal control mechanisms, and integrity culture. The study recommends strengthening multilayered oversight, improving firearms management systems, and institutionalizing firm, transparent sanctions to reinforce police professionalism and public trust.